Recommending a new building structure to alleviate environmental impact in tropical climates: increasing the use of wood in construction - Balasbaneh, Ali Tighnavard; Sher, Willy; Yeoh, David (Springer, 2022)
The construction sector is interested in considering environmental implications as necessary criteria for sustainability. In this regard, wood materials, especially engineering wood, are a promising choice for sustainable buildings. In some countries such as Malaysia, timber is rarely considered in the construction sector despite there being abundant access to wood. This is because of the scarcity of timber structures and the dominance of alternative materials such as steel and concrete. The cross-laminated timber-steel composite introduced in this research benefts both the wood and the steel markets leading to standardization and a more extensive market. At the same time, it contributes to environmentally friendly requirements. The main objective was to investigate timber applications in local construction and make proposals for its promotion. The new specimen described here could potentially enhance the strength of timber beams using steel plates. Four current structural methods have been chosen based on environmental and economic comparisons with a new composite structure